The practice of strengthening the base of a slab foundation of a multi-story building with soil-cement elements - Krysan, Vladimir; Krysan, Vitali; Hasenko, Anton (Academic journal Industrial Machine Building Civil Engineering, 2022)
The characteristic geotechnical conditions of modern high-rise construction are considered. The engineering and geological conditions of the site were analyzed. In particular, it was noted that loose soils lie up to a depth of 2.2 m, and below 13.0…13.5 – eolian-deluvial deposits (sandy and silty loams with a deformation modulus of 5…7 MPa). The territory is flooded. An effec-tive constructive-technological solution was tested using the drilling-mixing method of placing soil-cement elements to strength-en the base made of highly compressible clay soils under the slab foundation of a multi-story residential building with a parking lot under the conditions of the existing building. The results of tests of soil cement samples, which were selected during the execution of works, for uniaxial compression are presented.